Fusion of fingerprint recognition methods for robust human identification - Pereira, Sérgio [UNESP]; Marana, Aparecido Nilceu [UNESP]; Falguera, Juan Rogelio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Biometrics is one of the biggest tendencies in human identification. The fingerprint is the most widely used biometric. However considering the automatic fingerprint recognition a completely solved problem is a common mistake. The most popular and extensively used methods, the minutiae-based, do not perform well on poor-quality images and when just a small area of overlap between the template and the query images exists. The use of multibiometrics is considered one of the keys to overcome the weakness and improve the accuracy of biometrics systems. This paper presents the fusion of a minutiae-based and a ridge-based fingerprint recognition method at rank, decision and score level. The fusion techniques implemented leaded to a reduction of the Equal Error Rate by 31.78% (from 4.09% to 2.79%) and a decreasing of 6 positions in the rank to reach a Correct Retrieval (from rank 8 to 2) when assessed in the FVC2002-DB1A database. © 2008 IEEE.
Keywords: Error analysis; Evaporative cooling systems; Fusion reactions; Gait analysis; Image enhancement; Nuclear physics; Technology; Computational science and engineering; Equal Error Rate; Finger print recognition; Fingerprint recognition method; Fusion techniques; FVC2002; Human identification; International conferences; Multibiometrics; Query images; Biometrics